Front Cover: Multi‐omics approach to elucidate the gut microbiota activity: Metaproteomics and metagenomics connection. Issue 13 (2nd July 2018) - Guirro, Maria; Costa, Andrea; Gual‐Grau, Andreu; Mayneris‐Perxachs, Jordi; Torrell, Helena; Herrero, Pol; Canela, Núria; Arola, Lluís
Abstract : DOI:10.1002/elps.201700476 The cover picture shows the importance of gut microbiota in a dietary intervention and its relation with omics science. A hipercaloric diet can alter gut microbiota balance, but the supplementation with natural molecules such as hesperidin, a flavanone found in citrus fruits, can revert gut microbiota disruption. To evaluate this impact, a multiomic approach has emerged to decipher gut microbiota interaction with the host, using metagenomics and metaproteomics. Metagenomics assess the biodiversity in the gut; meanwhile metaproteomics reveal microbiota function in the host. The combination of both omics can give a real overview of the current health in the host.